Effect of Al2O3 nano sol content in Ni-Al2O3 composite coating on intermetallic compound formation and properties of Mg/Al soldered joints - Yingzong Liu; Yuanxing Li; Jinzhe Cui; Zongtao Zhu; Hui Chen (Journal of Magnesium and Alloys)
Combining Mg and Al dissimilar metals further reduces structural weight, but the formation of intermetallic compounds (IMCs) affects Al/Mg joint properties. To prevent IMCs, a Ni-Al2O3 composite coating was pre-plated on the Mg alloy substrate, and then Sn3.0Ag0.5Cu (SAC 305) solder was utilized to facilitate the joining of AZ31 Mg/6061 Al through ultrasonic-assisted soldering. We investigated the impact of Al2O3 nano sol content in the coating on microstructure evolution, IMCs formation, and mechanical properties. Results indicated that the Ni-Al2O3 composite coating effectively suppressed the Mg-Sn reaction, thereby preventing the formation of Mg2Sn IMC and significantly enhancing joint strength. In joints with a Ni-Al2O3 composite coating containing 50 mL/L Al2O3 nano sol, no Mg2Sn IMC was detected after 50 min of holding at 260 °C, achieving a maximum shear strength of approximately 67.2 MPa. Increasing the Al2O3 concentration further expanded the soldering process window. For the joint with Ni-Al2O3 (100 mL/L Al2O3 nano sol) composite coating held at 260 °C for 70 min, the coating was dissolved to a thickness of about 5.8 µm, but no Mg2Sn IMC was observed. The Ni-based solid solution formed near the coating/solder interface was strengthened, leading to fractures occurring within the SAC solder, and the maximum shear strength further increased to 73.9 MPa. The strengthening mechanism of the joints facilitated by using the Ni-Al2O3 composite coating was revealed by comparing with pure Ni-assisted joints. Therefore, employing a Ni-Al2O3 composite coating as a barrier layer represents a promising strategy for inhibiting IMC formation during the joining of dissimilar metals.